Characterization of Bragg Grating Lengths in Single-Mode Fiber for Strain Sensor Applications - Mat Salim, Muhammad Aizi; El Houari, Illiane; Bakhtiar, Hazri (Journal of Advanced Research Design, 2025)
This study presents the successful fabrication of Fiber Bragg Gratings (FBGs) using a 248 nm KrF Excimer Laser combined with the optical phase mask technique. The research focuses on investigating the effects of stress on Bragg grating length in single mode fibers (SMFs). A total of five FBGs, each with different grating lengths, were analyzed for strain sensitivity. The findings reveal a linear relationship between strain and Bragg grating length for all tested FBGs. Notably, the FBG with a grating length of 2.50 cm exhibited the highest strain sensitivity, however the strain sensitivity for all FBG grating lengths were found to be consistent. These results suggest the potential for optimizing FBG grating length in multimode fiber to enhance performance in strain-sensitive applications.